An Empirical Study on the Evaluation of Emotional Complexity in Daily Life - Dong, Boshi; Xu, Guangxing (Frontiers in Psychology, 2022)
Emotional complexity means diversity, universality, and differentiation of individual emotions. This research consisted of two studies to demonstrate the constitution of the emotional complexity. In Study 1, the participants were asked to use 10 emotional words to record the variation of emotions over 30 days in daily life. In Study 2, the experimental materials were enriched. The participants were required to note the emotions with the Positive and Negative Affect Schedule in a 3-day holiday—all the individuals in the two studies needed to record the most important emotional event. As a result, the youth experienced complex emotions every day. Emotional complexity indicators included covariation index (r), component index (Cpc and Cunshared), granularity index (Ge, Gp, and Gn), and variability index (Vp and Vn). A four-factor model reflected a good model fit, with 𝜒2/df = 0.33, CFI = 1.00, TLI = 1.03, RMSEA = 0.000 (0.00, 0.20), SRMR = 0.003, including positive differentiation, covariation of positive affect and negative affect, negative differentiation, and emotional variation. These indicators may reflect the complex experiences in everyday life. The results shed light on the emotional experience that can change greatly within 1 day and on episodes of emotional disruption resulting from an important event coupled with excessive excitement or extreme tension.